(untitled) - Lilya Avetisyan; Agnieszka Parlińska (Polityki Europejskie, Finanse i Marketing)
The paper presents possibilities of the use of leasing as an instrument of financing of innovation activities. At present times the issue of search of new ways of financial provision for innovation activity, which is the main factor of competitiveness of the enterprises, is of a particular importance. In the paper advantages of the leasing funding mechanism for innovation activities are presented, and the role of innovative leasing in modern conditions is revealed. The comparative analysis of regulation of leasing in a number of European countries is carried out, and also the analysis of the European leasing market is submitted. The structure and current trends of development of the domestic leasing market are considered. The main problems interfering development of leasing in Armenia are revealed. On the basis of the best European practices recommendations are provided, which will promote the use of leasing for stimulation of innovation activities of the enterprises in Armenia.